Go green at work - Kumar, M Sharath (Indian Horticulture, 2019)
"An office environment can nourish and support the human spirit as much as it can deny and suppress it. If our offices are humane, loving, green and sacred, then what is produced in those offices will have a sense of humanity and integrity… The act of turning the places green, where we work into places that we love, can transform our own lives, and will in turn positively affect the lives of everyone around us".